Case report of Ebstein’s anomaly in a young female - Rediet Dessalegne; Yoseph Bekele; Selamawit Getachew; Mekdelawit Birhanu (SAGE Open Medical Case Reports)
Ebstein’s anomaly, also known as Ebstein’s malformation, is a congenital heart defect that occurs in about 0.005% of live births and accounts for 0.3–0.6% of all congenital heart disease. It is due to delamination failure at embryologic state, or displacement of the leaflets from the ventricular myocardium. In people with Ebstein’s abnormality, the tricuspid valve does not close properly, leading to regurgitation. Here is the case report of a 24-year-old female patient who was diagnosed with Ebstein’s anomaly 5 years back and had been on follow-up. However, she missed appointments and discontinued the medication for 3 months. She presented with shortness of breath for 5 days, which occurred at rest, and generalized body weakness. Since she was in critical condition, she was admitted to the intensive care unit of the hospital. Subsequently, baseline and diagnostic investigations were done. The health care team initiated immediate treatment, and all available treatments were administered, and the patient’s condition improved. In this report, the first presentation of the woman was during adulthood and it was with heart failure even though most patients with Ebstein’s anomaly present during the early age of their life and with arrhythmia. Therefore, the main aim of this case report is to show the atypical presentation of Ebstein’s anomaly.